Density and body size of the larval stages of the invasive golden mussel (Limnoperna fortunei) in two neotropical rivers - Eilers,Vivianne (2011)
AIM: The present study involved an analysis of the monthly variations in the population densities and body sizes of the different stages of planktonic larvae of the invasive golden mussel (Limnoperna fortunei), in the rivers Paraguay and Miranda; METHODS: The study was carried out between February 2004 and January 2005. Monthly collection of the plankton samples was accompanied by physical, chemical and biological analyses of the water; RESULTS: The Miranda River presented higher values of calcium, pH, alkalinity, conductivity and total phosphorous. Larval density varied from 0-24 individuals.L-1 in the Paraguay River, with a peak in March of 2004, while in the Miranda River, densities varied between 0-9 individuals.L-1 with a peak in February of 2004. No larvae were encountered during the coldest months, May and June. No significant correlations were found between environmental variables and larval density in either river. Only the valved larval stages were recorded. The "D" and veliger forms were most abundant; umbonate larvae were rare in the Miranda River samples. Mean body sizes of "D", veliger and umbonate larval stages were, respectively, 111, 135 and 152 µm, in the Paraguay River, and 112, 134 and 154 µm in the Miranda River. Principal Components Analysis indicated positive relationships between "D" larval stage size and the ratio between inorganic and organic suspended solids, while negative relationships were found between larval size and calcium and chlorophyll- ; CONCLUSIONS: The larvae were recorded in the plankton during most of the year, with the exception of the two colder months. Neither densities nor larval stage body sizes were significantly different between the two rivers. Possible positive effects of food and calcium concentrations on body size were not recorded. This species may be adapted to grow in environments with elevated sediment concentrations.